Caregiver willingness to vaccinate their children against COVID-19: Cross sectional survey. Issue 48 (10th November 2020) - Goldman, Ran D.; Yan, Tyler D.; Seiler, Michelle; Parra Cotanda, Cristina; Brown, Julie C.; Klein, Eileen J.; Hoeffe, Julia; Gelernter, Renana; Hall, Jeanine E.; Davis, Adrienne L.; Griffiths, Mark A.; Mater, Ahmed; et al.
Highlights: About two thirds of caregivers intend to vaccinate their children against COVID-19. Most common reason for acceptance was to protect the child. Most common reason for refusal was the vaccine's novelty. Child age, chronic illness, vaccination history affects willingness. Caregiver gender, vaccination history, concern about infection affect willingness. Abstract: Background: More than 100 COVID-19 vaccine candidates are in development since the SARS-CoV-2 genetic sequence was published in January 2020. The uptake of a COVID-19 vaccine among children will be instrumental in limiting the spread of the disease as herd immunity may require vaccine coverage of up to 80% of the population. Prior history of pandemic vaccine coverage was as low as 40% among children in the United States during the 2009 H1N1 influenza pandemic. Purpose: To investigate predictors associated with global caregivers' intent to vaccinate their children against COVID-19, when the vaccine becomes available. Method: An international cross sectional survey of 1541 caregivers arriving with their children to 16 pediatric Emergency Departments (ED) across six countries from March 26 to May 31, 2020. Results: 65% (n = 1005) of caregivers reported that they intend to vaccinate their child against COVID-19, once a vaccine is available. A univariate and subsequent multivariate analysis found that increased intended uptake was associated with children that were older, children with no chronic illness, when fathers completed the survey, children up-to-date on their vaccination schedule, recent history of vaccination against influenza, and caregivers concerned their child had COVID-19 at the time of survey completion in the ED. The most common reason reported by caregivers intending to vaccinate was to protect their child (62%), and the most common reason reported by caregivers refusing vaccination was the vaccine's novelty (52%). Conclusions: The majority of caregivers intend to vaccinate their children against COVID-19, though uptake will likely be associated with specific factors such as child and caregiver demographics and vaccination history. Public health strategies need to address barriers to uptake by providing evidence about an upcoming COVID-19 vaccine's safety and efficacy, highlighting the risks and consequences of infection in children, and educating caregivers on the role of vaccination.